Gadolinium doped vanadium dioxide : synthesis and thermochromic properties - Yang, Man (2014)
Energy conservation has always been a great concern for the whole world. Thermochromic coatings materials used for energy-saving windows can greatly reduce the heating and air conditioning cost. Vanadium (IV) Dioxide (VO2) is the most promising thermochromic materials can be used in this application; it has a phase transition temperature (τc) at 68oC which is closest to the ambient temperature. Previous studies have showed that doping of some particular elements can help to reduce τc of VO2. The aim of this project is to investigate the rare earth element Gadolinium doping effects on morphology, crystalline phase and thermochromic properties of Vanadium Dioxide by using a direct, simple solution method. The synthesized coating films were characterized by X-ray diffraction (XRD), Ultraviolet - visible light – near infrared spectroscopy (UV-Vis-NIR) and Field emission scanning electron microscopy (FESEM). Thus the doping effect of Gd on phases, surface morphology as well as thermochromic properties on VO2 can be found. Transition temperature of VO2 was reduced with Gd doping. However, the effect of different doping levels from 0 at% to 4.0 at% was still needed to study. ΔTsol increased 30% from 0 at% to 1.0 at% Gd doping, while Gd doping was not observed to effectively increase Tlum.